The Effect of Social Media Marketing, E-WoM on Purchase Intention Mediated by Brand Image and Brand Trust: Halal Product FnB MSMEs in Malang City - Iva Khoiril Mala; Sudarmiatin; Ludi Wishnu Wardana (Indonesian Journal of Business Analytics, 2023)
The aim of this research is to evaluate the most popular internet activity among Indonesian internet users, namely social networking. Social media that is currently popular among people is Instagram, Tiktok, Twittwer, Facebook, etc. This research uses quantitative methods with an explanatory research approach. The analysis technique for this research is purposive sampling. The research population is all Halal FnB MSMEs in the city of Malang and the research sample is 380 Instagram followers. Data analysis using SEM-PLS with SmartPLS 3.0. The research results show that hypotheses 1 to hypothesis 12 are that social media marketing and E-WoM have a positive and significant effect on purchasing decisions mediated by brand trust and brand image.